IMPLEMENTASI EVALUASI DIRI MADRASAH BERBASIS APLIKASI E-RKAM DALAM MENINGKATKAN MUTU DI MTS AL KHAIRIYAH KALIAWI KOTA BANDAR LAMPUNG - Nurul Istiqomah; Fisman Bedi; Ahmad Fauzan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to describe the Implementation of Madrasah Self Evaluation Based on E-Rkam Application in Improving Quality at MTS Al Khairiyah Kaliawi, Bandar Lampung City. This research uses qualitative research with qualitative descriptive methods. The primary sources of this research are the principal and the teachers. While secondary sources in this study are books, documents, and scientific articles related to research. Data collection techniques using observation interviews and documentation. Data validity test using data triangulation. And data analysis using Miles and Huberman analysis techniques, namely by codifying data, presenting data, and drawing conclusions. The results showed that the process of planning and organizing the implementation of the e-RKAM application was in accordance with the guidelines for use and standard operating procedures for e-RKAM, then the success in improving the quality of education was in the good category by looking at the data comparison between the Quality Achievement Performance Score in 2022 and 2023.